Comparing Subjective Contours for Kanizsa Squares and Linear Edge Alignments ('New York Titanic' Figures). (September 2014) - Gillam, Barbara; Marlow, Phillip J
One current view is that subjective contours may involve high-level detection of a salient shape with back propagation to early visual areas where small receptive fields allow for scrutiny of relevant details. This idea applies to Kanizsa-type figures. However, Gillam and Chan (2002 Psychological Science, 13, 279–282) using figures based on Gillam's graphic 'New York Titanic' (Gillam, 1997 Thresholds: Limits of perception . New York: Arts Magazine) showed that strong subjective contours can be seen along the linearly aligned edges of a set of shapes if occlusion cues of 'extrinsic edge' and 'entropy contrast' are strong. Here we compared ratings of the strength of subjective contours along linear alignments with those seen in Kanizsa figures. The strongest subjective contour for a single set of linearly aligned shapes was similar in strength to the edges of a Kanizsa square (controlling for support ratio) despite the lack of a salient region. The addition of a second set of linearly aligned inducers consistent with a common surface increased subjective-contour strength, as did having four rather than two 'pacmen' in the Kanizsa figure, indicating a role for surface support. We argue that linear subjective contours allow for the investigation of certain occlusion cues and the interactions between them that are not easily explored with Kanizsa figures.